Strategic Management and Market Feasibility of Tegal Tourism: A Digital Transformation Perspective - Dwi Novita Cahyaningtyas Permatasari; Deddy Kurniawan Halim; Dinar Sukma Pramesti; Vivi Vivi (International Journal of Management Science and Information Technology, 2026)
Digital transformation in the tourism sector has accelerated the emergence of technology-driven platforms that enable the end-to-end integration of tourism experiences. This study examines the market feasibility and strategic management implications of the Tegal Tourism platform, which comprises four main subsystems: Virtual Tour, Tourism Marketplace, Mitra Jelajah (partner ecosystem), and an AI-based chatbot. Adopting a mixed-methods approach, the study combines survey data from 116 respondents with in-depth interviews, FGDs, and prototype testing. Market feasibility is evaluated across five key dimensions, namely market demand and trends, consumer segmentation and user profiles, competitor and substitute product analysis, go-to-market and distribution strategies, and quantitative demand estimation. The findings reveal that 56.9% of respondents are familiar with virtual tours, 70% are interested in exploring tourism through such technology, and more than 77% indicate a likelihood of making transactions after a virtual experience, demonstrating strong online-to-offline (O2O) conversion potential. Additionally, 94% of respondents primarily use smartphones, highlighting the importance of a mobile-first strategy. Overall, the platform demonstrates high market feasibility, supported by strong user interest, digital readiness, and significant transaction potential. Four of the five dimensions meet the feasibility criteria, while consumer segmentation and user profiles remain at a medium-to-high risk level and require targeted mitigation. This study contributes to strategic management and digital tourism literature by offering an integrated feasibility framework and practical insights for strengthening digital tourism ecosystems and MSME participation.